Open versus Arthroscopic Scapholunate Ligament Repair: A Systematic Review - Zhou, Joanne; Vazquez, Frank; Zhou, Brian; Gulzar, Musab; Ross, Owen; Gottschalk, Michael B.; Suh, Nina; Wagner, Eric R. (Journal of Wrist Surgery, 2025)
Scapholunate interosseous ligament (SLIL) injuries have traditionally been treated via open approaches. Recent arthroscopic techniques have improved the ability to access the SLIL while preserving local blood supply and ligaments. Here, we present a systematic review comparing outcomes after arthroscopic versus open SLIL repair.A systematic search of PubMed was conducted for primary research articles evaluating open or arthroscopic SLIL repair. Inclusion criteria were primary articles examining open or arthroscopic repair of SLIL injuries. Data extracted included surgical interventions and indications, time from injury to surgery, length of follow-up, range of motion (ROM), reoperations, patient-reported outcome measures (PROMs), radiographic results, and complications.Out of 226 studies screened, 15 met inclusion criteria, encompassing 982 SLIL repairs (827 arthroscopic, 155 open). The frequency-weighted mean follow-up was 41 months, with a mean age of 34 years (range 14–68). PROMs were significantly improved in arthroscopic compared with open repairs, with visual analog scale (VAS) scores of 1.13 versus 4.69 (p < 0.05), Disabilities of the Arm, Shoulder, and Hand (DASH) scores of 9.93 versus 21.93 (p < 0.05), and Mayo scores of 87.55 versus 80.28 (p < 0.05). Functional outcomes also revealed increased range of motion and strength in the arthroscopic group: flexion (67.04 degrees vs. 51.73 degrees), extension (72.56 versus vs. 51.97 degrees), and strength (41.94 kg vs. 34.59 kg; all p < 0.05). Radiographic outcomes demonstrated a significant albeit smaller postoperative scapholunate (SL) angle, with arthroscopic repairs at 54.08 degrees and open repairs at 59.10 degrees (p < 0.05).Arthroscopic SLIL repair is associated with improved pain, ROM, strength, and PROMs compared with open repair, along with a more favorable postoperative SL angle. These findings support the potential benefits of arthroscopic approaches in managing SLIL injuries and may inform future treatment algorithms.
Keywords: scapholunate interosseus ligament; arthroscopic; open; systematic review; repair